The Relationship Among BDNF Val66Met Polymorphism, Plasma BDNF Level, and Trait Anxiety in Chinese Patients With Panic Disorder - Chu, Lijun; Sun, Xia; Jia, Xiaoju; Li, Dazhi; Gao, Ping; Zhang, Yong; Li, Jie (Frontiers in Psychiatry, 2022)
Background Brain-derived neurotrophic factor (BDNF) is a candidate for susceptibility locus of Panic disorder (PD). However, the findings about the role of the BDNF Val66Met variant in PD were not consistent. Till now, the relationship between BDNF Val66Met polymorphism and anxiety-related traits in PD patients has been rarely explored. This study aimed to explore the relationship among BDNF Val66Met polymorphism, plasma BDNF level and anxiety-related trait in Chinese PD patients. Method This multi-center study included 116 PD patients and 99 health controls. We detected single-nucleotide polymorphism (SNP) of BDNF rs6265 (Val66Met) and BDNF plasma level in the two groups. In addition, PD patients were administered the State-Trait Anxiety Inventory (STAI), Panic Disorder Severity Scale-Chinese Version (PDSS-CV) and Hamilton Anxiety Rating Scale (HAMA-14). Quantitative comparison of the differences of BDNF concentration among subjects with different genotypes and association between BDNF Val66Met genotype and trait anxiety were performed. Results There were no significant differences in the genotype frequency (p = 0.79) or allele frequency (p = 0.88) between PD patients and health controls. BDNF plasma levels of PD patients were significantly lower than those in control group (p = 0.003). BDNF plasma levels of the Met/Met genotype were significantly lower than those of Val/Met genotype in PD patients (p = 0.033). PD patients carried Met/Met genotype showed significantly higher scores in STAI trait compared to those carried Val/Val genotype (p = 0.045) and Val/Met genotype (p = 0.018). STAI trait scores of PD patients with agoraphobia were significantly higher than those of patients without agoraphobia (p < 0.05). The ANCOVA showed that the dependent variable STAI trait score was significantly affected by factor “genotype” (Val/Val, Val/Met, Met/Met, p = 0.029), and covariate “agoraphobia” (p = 0.008). In this model, 11.5% of the variance of the STAI trait score was explained by the BDNF genotype. Contrast analysis showed STAI trait scores of Met/Met subjects were significantly higher than those of Val/Met (p = 0.018) and Val/Val individuals (p = 0.045). Conclusion We found that anxiety trait was associated with the BDNF polymorphism in PD patients. BDNF Met/Met genotype may decrease plasma BDNF level and increase trait anxiety in panic disorder.